A critical inventory of the family Amaranthaceae s.str. in Saudi Arabia - Hassan, Walaa A.; Al-Shaye, Najla A.; Iamonico, Duilio (Phytotaxa, 2023)
The aims of the present study are to assess and update the floristic diversity of Amaranthaceae s.str. in Saudi Arabia. A total number of 33 taxa were indentified including 28 species, 4 subspecies, and 7 varieties. The richest genus is Amaranthus with 16 taxa (12 species); Aerva and Alternanthera have 3 species each; Achyranthes and Celosia 2 species each; 6 genera (Digera, Gomphrena, Nothosaerva, Psilotrichum, Pupalia, Saltia) include just one species each. Most of the taxa are native (18, 54.55%), 14 (42.42%) are aliens (6 casual taxa, 5 naturalized, and 1 invasive), one (Alternanthera sessilis) is here considered as doubtfully native, two (Amaranthus tricolor, Gomphrena globosa) are found only in cultivation. Two species (Amaranthus tortuosum, Pupalia lappacea var. lappacea) are excluded from the national flora. Diagnostic keys at genus, species, and infraspecific ranks are provided. The following names are lectotypified: Achyranthes argentea var. obovata (G; isolectotype at HBG), Achyranthes fruticosa var. pubescens (G), Achyranthes papposa (C; isolectotypes at C and BM), Achyranthes polystachya (BM), Aerva javanica var. bovei (FI), Achyranthes lanata (illustration by Burman), Digera arvensis (C; isolectotype at C), Psilostachys gnaphalobryum (TUB; isolectotypes at GOET, HBG, HEID, JE, MEL, MPU, P, and TUB), Telanthera bettzickiana (LE).